Work-life balance, role conflict and the UK Sport psychology consultant - Waumsley, J. A.; Hemmings, B.; Payne, S. M. (The Sport Psychologist, 2010)
To date there has not been a comprehensive discussion in the literature of worklife balance for the sport psychology consultant. The number and complexity of roles often undertaken by consultants may lead to potential stress if roles conflict. Underpinned by Role Theory (Kahn, Wolfe, Quinn, Snoek, & Rosenthal, 1964) and the Spillover Hypothesis (Staines, 1980) this paper draws on the work-life balance literature to present the potential conflicts and ethical dilemmas experienced by the sport psychology consultant as a result of conducting multiple roles. With an applied focus, ways of obtaining work-life balance are suggested through a psychological model outlining personal organizational skills, ongoing supervision/mentoring and reflective practice, and safeguarding leisure time. While certain aspects of the model are built on the UK experience, many of the suggestions will be applicable to sport psychology consultants regardless of their location. Ideas for future research directions involving exploring conflicting roles, work-life balance and coping issues for the sport psychology consultant are presented.